Relationship between moderate-to-vigorous, light intensity physical activity and sedentary behavior in a prospective cohort of older French adults: a 18-year follow-up of mortality and cardiovascular events ─ the PROOF cohort study - Dupré, Caroline; Brégère, Marlène; Berger, Mathieu; Pichot, Vincent; Celle, Sébastien; Garet, Martin; Fundenberger, Hervé; Barth, Nathalie; Guyot, Jessica; Bongue, Bienvenu; Barthélémy, Jean-Claude; Roche, Frédéric; et al. (Frontiers in Public Health, 2023)
Background: It is well documented that moderate-to-vigorous intensity physical activity (MVPA) is effective in the prevention of major chronic diseases. Even though the current international physical activity (PA) guidelines still mainly focus on MVPA, the topic of the most recent epidemiological studies has shifted from MVPA to light intensity physical activity (LPA), owing to the necessity of promoting all activities vs. sedentary behavior (SB). However, the evidence remains currently limited. Thus, the clarification of the effects of LPA and the close relationship with SB is crucial to promote public health. Method: PA and SB were assessed by a validated self-administered questionnaire (POPAQ) investigating 5 different types of PA during the 7 previous days. PA was measured in metabolic equivalent of task (MET)-h, which refers to the amount of energy (calories) expended per hour of PA. SB was measured in hour/day. Medical histories and examinations were taken during each clinical visit to determine clinical events. All-cause mortality was established using the same procedure and by checking local death registries. The relationships between the intensity of PA (light, moderate to vigorous) and mortality and between the periods of SB and mortality or CV events were analyzed by splines and COX models, adjusted for sex and year of birth. Results: From the 1011 65-year-old subjects initially included in 2001 (60% women), the last 18-year follow-up has been currently completed since 2019. A total of 197 deaths (19.2%, including 77 CV deaths) and 195 CV events (19.3%) were reported. Averages (standard deviation) of MVPA, LPA and SB were respectively 1.2 h/d (0.3), 5.8 h/d (1.1) and 6.6 h/d (2.3). For all-cause deaths, as well as CV deaths, the splines were significant for LPA (p=0.04 and p=0.01), and MVPA (p<0.001 and p<0.001), but not for SB (p=0.24 and p=0.90). There was a significant reduction in CV events when SB was decreasing from 10.9 to 3.3 h/d. Conclusion: The PROOF cohort study shows a clear dose-response between the dose of LPA, MVPA, SB and risk of mortality. These findings provide additional evidence to support the inclusion of LPA in future PA guidelines.